THE INFLUENCE OF TAKING A PART TIME JOB TOWARDS STUDENTS’ LEARNING MOTIVATION AT THE SEVENTH SEMESTER STUDENTS OF ENGLISH EDUCATION DEPARTMENT OF UIN ALAUDDIN MAKASSAR - Sitti Nurpahmi; Andi Mulyana Thamrin (Universitas Islam Negeri Alauddin Makassar, 2016)
The main objective of this research was to find out the influence of taking a part time job towards students’ learning motivation at the seventh semester students of English Education Department. The researcher applied quantitative and qualitative descriptive method. The population of this research was the seventh semester students of English Education Department and the sample were students who took part time jobs in each class of the seventh semester students’ academic year 2012 which consisted of 20 students. The data were collected through questionnaire and interview. The result of the data was indicated that there were positive influences of taking a part time job towards students’ learning motivation. It was proven by the mean score of total number of all questions as 43.9 which was classified as very high. The result of interview was some students liked their part time jobs because they could be more experienced in teaching, could obtained money for their daily needs, and they said that there was influence of taking a part time job towards their learning motivation improvement. It was proven by the lists of students’ GPA which the most were increase. The positive influences also from the hours of students’ work which were not more than 20 hours per week where it was appropriate with the rule in Australia. Based on the result, the researcher concluded that taking a part time job has some influences especially in improving students’ learning motivation.